1989
DOI: 10.1136/bjo.73.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Extensive argon laser photocoagulation in the treatment of proliferative diabetic retinopathy.

Abstract: SUMMARY A group of 20 patients (28 eyes) with proliferative retinopathy who required extensive argon laser photocoagulation to induce regression of new vessels is presented. The mean number of burns applied to each eye was 7225, with a maximum of 11513. These were delivered in a mean of nine sessions over a mean period of 22.9 months. Twenty-five eyes (89%) had a final visual acuity of 6/18 or better. The remaining three eyes (11%) had severely reduced vision attributable to complications of proliferative diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
1
12
0
3
Order By: Relevance
“…20,21,33,34 However, substantial regression of new vessels may take weeks after completion of PRP, and in up to one-third of cases, new vessels continue to grow despite initial PRP. 21,34 In these cases, vitreous haemorrhage may induce visual loss and prevent complete laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21,33,34 However, substantial regression of new vessels may take weeks after completion of PRP, and in up to one-third of cases, new vessels continue to grow despite initial PRP. 21,34 In these cases, vitreous haemorrhage may induce visual loss and prevent complete laser.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Long intervals between PRP sessions and the variable amount of time required for a favourable response may increase the incidence of complications due to the progression of PDR. 18,20 In fact, a single episode of PRP or shorter intervals between PRP episodes, although desirable in severe PDR and when the patient must travel long distances for treatment, are often associated with acute visual disturbances due to exudative choroidal detachment, retinal detachment, and macular oedema. [21][22][23][24] The purpose of this retrospective study was to evaluate the effectiveness of intravitreal bevacizumab on RN in patients with PDR as a base for future studies in which bevacizumab may be used as an adjuvant treatment to PRP for PDR.…”
Section: Introductionmentioning
confidence: 99%
“…Our results for 20-ms PRP treatment show results similar to this study; however, Reddy and co-workers used krypton red and/or cryotherapy as supplemental treatment modalities. In a study of eyes with NVD only, Aylward and co-workers 20 reported 64% complete regression using conventional (200-500 mm) 100-ms PRP treatment; however, a mean of 7225 laser shots were required (range 5279-11 513 burns) and this resulted in confluent laser scarring. The application of confluent PRP is outwith the current Royal College of Ophthalmologists recommended laser treatment guidelines.…”
Section: -19mentioning
confidence: 99%
“…In addition to the above, PRP induces posterior vitreous detachment in 50% cases and in the large majority this is eventless. A small percentage of these cases may show vitreous bleeding or even TRD during completion of PRP if it is too aggressive and spaced closely 40. We therefore understand that in the large majority of cases (77% in our series) a balance is established between the beneficial effect of laser on retina and the damaging effect of diabetic vitreopathy.…”
Section: Discussionmentioning
confidence: 82%